1988
DOI: 10.1192/bjp.152.6.775
|View full text |Cite
|
Sign up to set email alerts
|

The Camberwell Collaborative Depression Study III. Depression and Adversity in the Relatives of Depressed Probands

Abstract: The relationship between life events and depressive disorder was assessed in 83 families ascertained through depressed probands. Contrary to expectation and to previous suggestions, we found no inverse relationship between the presence of familial loading and reactivity to stress. Thus the relatives of probands whose onset of depression followed life events or chronic difficulties had slightly higher lifetime rates of depression than the relatives of probands whose onset was not associated with adversity. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
5

Year Published

1993
1993
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(79 citation statements)
references
References 17 publications
5
68
1
5
Order By: Relevance
“…8 Considered together, early and proximal social factors explain a large proportion of depression in population-based samples. 8 However, these social factors account for relatively smaller proportion of depression in clinically ascertained samples 9,10 and fail to explain the grater differences in risk of depression between monozygotic compared to dizygotic twins. 11,12 The evidence for genetic influences on depression consists primarily of twin studies.…”
Section: The Interacting Causes Of Depressionmentioning
confidence: 99%
“…8 Considered together, early and proximal social factors explain a large proportion of depression in population-based samples. 8 However, these social factors account for relatively smaller proportion of depression in clinically ascertained samples 9,10 and fail to explain the grater differences in risk of depression between monozygotic compared to dizygotic twins. 11,12 The evidence for genetic influences on depression consists primarily of twin studies.…”
Section: The Interacting Causes Of Depressionmentioning
confidence: 99%
“…22 We found no statistically significant differences in the reported gene-environment interaction when women were compared to men. Family history of psychological problems has been associated with both exposure 36 and outcome, 37 and thus should remain in the model. The independence from family history of our reported gene-environment interaction may suggest that there could be some specific role for the 5HTTLPR genotype (or the serotonin transporter gene) in its modification of the risk effect for depression conferred by previous TLEs.…”
Section: Novelty and Interestmentioning
confidence: 99%
“…For example, Bebbington and colleagues McGuffin et al, 1988) have shown that levels of SLEs are increased in the relatives of depressed patients versus controls, although Farmer and colleagues (Farmer et al, 2000) suggested that familial similarities in SLEs with depression may largely result from shared experiences.…”
mentioning
confidence: 99%